Yield Response of Cowpea (Vigna unguiculata L.) to Poultry Waste Application With Different Rates of Potassium and Phosphorus Inorganic Fertilizers - Iwanthika, G.M.S.; Seran, Thayamini H. (International Journal of Environment, 2023)
Poultry waste is a rich source of nitrogen nutrient compared to other elements. In crop cultivation, combined application of organic manures and inorganic fertilizers increase soil nutrients which are available to plants. Cowpea (Vigna unguiculata L. walp) is a significant grain legume production and it is used as a source of low cost protein for human consumption particularly in the developing countries. Thus, the experiment was conducted to determine the effects of poultry waste with phosphorus and potassium inorganic fertilizers on seed yield of cowpea (Vigna unguiculata L.). The pot experiment was designed in a Completely Randomized Design (CRD) with six treatments and seven replicates. Treatments included T1 – 100% inorganic fertilizer [35 kg ha-1 urea, 100 kg ha-1 triple superphosphate (100% TSP) and 75 kg ha-1 muriate of potash (100% MOP)], T2 – 10 t ha-1 poultry waste alone, T3 – 10 t ha-1 poultry waste + 25% TSP + 25% MOP, T4 – 10 t ha-1 poultry waste + 50% TSP + 50% MOP, T5 – 10 t ha-1 poultry waste + 75% TSP + 75% MOP, T6 – 10 t ha-1 poultry waste + 100% TSP + 100% MOP. The result confirmed that the poultry waste with potassium and phosphorus inorganic fertilizers had significant differences (P<0.05) on most of the agronomic parameters tested in this experiment. Results revealed that application of 10 t ha-1 poultry waste with 100% TSP and 100% MOP treatment (T6) showed the best treatment for cowpea yield in term of seed yield. But significant variation on seed yield was not observed between T5 (10 t ha-1 poultry waste with 75% TSP and 75% MOP treatment) and T6 (10 t ha-1 poultry waste + 100% TSP + 100% MOP) treatments. Therefore, application of 10 t ha-1 poultry waste reduces the usage of inorganic fertilizers (urea by 100%, TSP by 25% and MOP by 25%) for obtaining better seed yield in cowpea cultivation.